The Role of Proactive Leaders' Behavior in Job Engagement: A Survey Study of the Opinions of a Sample of Employees in the Passport Directorates in the Kurdistan Region of Iraq - محمد فرج قرداغي, كاوه; احمد عزيز, ديلمان (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
The current research aims to shed light on the role of the proactive behavior of leaders with its dimensions (vocal behavior, assuming responsibility, individual creativity, prevention of problems) in achieving job Engagement for workers in the Passports Directorates in the Kurdistan Region of Iraq. The study followed the analytical descriptive approach, where a questionnaire was designed to collect data. The study population consisted of (493) workers.as (283) questionnaires were distributed to the research sample represented by the employees of the researched directorates, and the research sample was chosen randomly. (270) questionnaires were retrieved, with a general response rate of (95%), and after excluding (2) questionnaires that were not valid for statistical analysis, the number of questionnaires valid for statistical analysis reached (268), with an average of (99%) of the number of retrieved questionnaires. Some statistical tests were used through the use of the statistical program for the social sciences (SPSS-V24) and the program (SmartPLS v.4), the simple linear correlation coefficient (Pearson Correlation), and the structural equation modeling method. The results showed a positive correlation and effect between the variables. From which it is concluded that whenever leaders possess proactive behaviors in the researched directorates, this leads to improving the capabilities and capabilities of that organization in achieving the dimensions of job Engagement. Based on the results of the research, a number of recommendations were presented, the most important of which is that the administrative leaders in the researched directorates should adopt proactive behavior practices due to their importance in bringing about positive changes in the work environment, which is reflected positively in the results of the institution.